Improved uptake of RiceAdvice digital application for increasing farmers’ yield and income while reducing environmental impact of rice cultivation in Mali - Diallo, Aboubacar; Dossou-Yovo, Elliott Ronald; Samuel, Guindo; Akpoffo, M. Marius; Doumbia, Salif (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
This research assessed the dissemination methods of RiceAdvice, the factors influencing farmers' decisions to use, and its impacts on rice yield, farmers' income, food consumption score, and estimated greenhouse gas emissions in Mali. A total of 95,749 farmers, including 34,470 women (36%), benefited from RiceAdvice recommendations and were assisted by 120 young service providers in implementing these recommendations on their fields. Farmers' decisions to use RiceAdvice recommendations were influenced by formal education, farm size, and membership in farmers' organizations. Users of RiceAdvice recommendations witnessed an additional 1044 kg/ha in rice yield, an increased income of 224,453 XOF/ha, and a noteworthy rise of 9 in the food consumption score. The application of RiceAdvice resulted in a reduction of urea fertilizer by 34 kg/ha and NPK fertilizer by 48 kg/ha, consequently decreasing greenhouse gas emissions by 35 kg CO2 eq/ha. When the aggregated benefits of RiceAdvice application were considered over the entire cultivated area of the beneficiaries, the use of RiceAdvice recommendations led to an increase in rice production by 14,957 tons, a boost in farmers' income by 3.21 billion XOF (5.4 million USD), and a reduction in urea fertilizer use by 487,108 kg and NPK fertilizer use by 687,682 kg. Consequently, greenhouse gas emissions were estimated to be reduced by 487,108 kg CO2 eq.